PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING UNTUK MEMILIH JURUSAN PADA KAMPUS NEGERI - Harvey Guharelvino Prabowo; Theresiawati Theresiawati (Jurnal Ilmiah Matrik, 2023)
Students in grade twelfth high school must be able to determine their individual student interests to be able to continue further studies at university. But there are still many students who have not been able to determine their specialization even though they have sufficient understanding and knowledge of learning during high school. This study aims to apply simple additive weighting and calculation of the tightness capacity of each specialization major on a public campus in making a Decision Support System in determining student majors in the Angkasa High School environment. By paying attention to the weight and each criterion for the specialization major, then calculate with the tight capacity of the specialization department on each state campus so that the results issued by the calculation have provided decision support for students to determine specialization and state campuses more precisely. The decision support system uses the Kotlin programming language and Android-based NoSQL MongoDB database. The results of the manual calculation of the Simple Additive Weighting and Opportunity method with a decision support system reach 99% according.